2008
DOI: 10.1056/nejmoa072488
|View full text |Cite
|
Sign up to set email alerts
|

A Parkinsonian Syndrome in Methcathinone Users and the Role of Manganese

Abstract: Our observation of a distinctive extrapyramidal syndrome, changes in the MRI signal in the basal ganglia, and elevated blood manganese levels in methcathinone users suggests that manganese in the methcathinone solution causes a persistent neurologic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 33 publications
6
141
1
3
Order By: Relevance
“…In a follow-up survey of 34 individuals initially discussed with a poisons center in Israel following use of "Hagigat" capsules, which contain cathinone, common unwanted effects included gastrointestinal (nausea, vomiting, diarrhea), cardiovascular (tachycardia, hypertension), neurological (headache, restlessness, anxiety), and respiratory (dyspnea) [13]. There have been numerous reports of "parkinsonism" like neurological toxicity developing following intravenous injection of "Russian Cocktail" across Russia and a number of former Eastern European countries [16][17][18][19][20][21][22]. These individuals had been injecting methcathinone, and initially it was thought that their symptoms directly related to this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up survey of 34 individuals initially discussed with a poisons center in Israel following use of "Hagigat" capsules, which contain cathinone, common unwanted effects included gastrointestinal (nausea, vomiting, diarrhea), cardiovascular (tachycardia, hypertension), neurological (headache, restlessness, anxiety), and respiratory (dyspnea) [13]. There have been numerous reports of "parkinsonism" like neurological toxicity developing following intravenous injection of "Russian Cocktail" across Russia and a number of former Eastern European countries [16][17][18][19][20][21][22]. These individuals had been injecting methcathinone, and initially it was thought that their symptoms directly related to this.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals had been injecting methcathinone, and initially it was thought that their symptoms directly related to this. However, on further investigation and detailed toxicological analysis, it was found that the solutions being injected had high concentrations of manganese and that, in fact, the extrapyramidal features were related to manganese toxicity [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have similar pharmacological properties to the popular stimulants such as cocaine, amphetamines and 3,4-methylenedioxy-N-methylamphetamine (MDMA) [4][5][6][7][8][9]. Toxicity [10][11][12][13][14] and some deaths [15][16][17] have been associated with the recreational use of these drugs. These drugs are sometimes sold online under a variety of names, such as "bath salts" and "plant food" [18], and users often do not know the actual active ingredients when using these drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…en torno a 1991, como droga de inyección endovenosa, fabricándose mediante la oxidación de efedrina y pseudoefedrina, obtenidas éstas fácilmente al ser medicamentos de dispensación sin receta 40 . A partir de 2003, en Lituania comenzaron a detectarse casos de parkinsonismo entre consumidores de esta sustancia, atribuidos a su contaminación con manganeso en el proceso de fabricación 41 …”
Section: Mefedronaunclassified